SINERGI ORIENTASI PASAR DAN TEKNOLOGI UNTUK KEUNGGULAN BERSAING BERKELANJUTAN UMKM MAKANAN - Sugih Prakoso (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
This study aims to analyze the influence of Market Orientation and Technology on Sustainable Competitive Advantage in the food MSME (Micro, Small, and Medium Enterprises) sector in West Java Province. The study is grounded in the need for MSMEs to maintain a competitive position amid rapidly changing market dynamics, technological advancements, and increasingly complex consumer demands. A quantitative research approach was employed, utilizing Structural Equation Modeling (SEM) with SmartPLS software. The respondents consisted of owners or managers of active food MSMEs operating in 27 regencies and cities across West Java. The findings reveal that both market orientation and technology utilization have a positive and significant impact on sustainable competitive advantage. Market orientation enhances responsiveness to consumer needs and supports product innovation, while technology contributes to operational efficiency, service speed, and information integration. These results highlight that the synergy between market strategies and technological capabilities forms a strategic foundation for building long-term competitive advantage. The study recommends that MSME actors invest in technology-based innovation and strengthen market understanding to sustain their existence and competitiveness in a dynamic business environment.